Development of a mammalian neurosensory full‐thickness skin equivalent and its application to screen sensitizing stimuli - Matthew Freer; Nicole Darling; Kirsty Goncalves; Kevin J. Mills; Stefan Przyborski (Wiley, 2023)
Abstract Human skin equivalents (HSEs) are an increasingly popular research tool due to limitations associated with animal testing for dermatological research. They recapitulate many aspects of skin structure and function, however, many only contain two basic cell types to model dermal and epidermal compartments, which limits their application. We describe advances in the field skin tissue modeling to produce a construct containing sensory‐like neurons that is responsive to known noxious stimuli. Through incorporation of mammalian sensory‐like neurons, we were able to recapitulate aspects of the neuroinflammatory response including secretion of substance P and a range of pro‐inflammatory cytokines in response to a well‐characterized neurosensitizing agent: capsaicin. We observed that neuronal cell bodies reside in the upper dermal compartment with neurites extending toward the keratinocytes of the stratum basale where they exist in close proximity to one another. These data suggest that we are able to model aspects of the neuroinflammatory response that occurs during exposure to dermatological stimuli including therapeutics and cosmetics. We propose that this skin construct can be considered a platform technology with a wide range of applications including screening of actives, therapeutics, modeling of inflammatory skin diseases, and fundamental approaches to probe underlying cell and molecular mechanisms.